Processos formativos e ciclo de vida de uma professora alfabetizadora - Feller, Elinara Leslei (2008)
This study is linked to the research line Professional Formation, Knowledge and Development of the Post-Graduation Program of Federal University of Santa Maria and focuses on the Life History of a training teacher with 30 years in the training class. The general objective is to investigate formation processes and life cycle of a training teacher and the elements that have influenced her permanence for 30 years in the training class . In a qualitative approach, through the Biographical Method Life History, the methodological proceedings for the information production are defined from oral autobiographical narrative and semi-structured interview. The autobiography contributes by giving visibility to the life histories, since, when the professor rememorizes her work, the meeting with her personal life helps her to understand, according to Moita (1992), the professional role in life and the role of life in the profession . The interlocutor of this research is a teacher who works for 30 years in the class. From her life history, her memories of becoming a training teacher and keep teaching how to read, mobilize in founding out competences and experiences that were being built throughout her schooling, her formation processes and all her professional life cycle. To perceive the Life History as a possibility of reflecting about memories related to transformation times brings us the opportunity of going to training practices, as well as the elements that guides this teacher to keep 30 years training. In the final considerations, it is highlighted the elements that influence the interlocutor of this research in being and keeping working in training classes in many phases of her professional life cycle, as a satisfied and motivated person with the teaching profession. Besides that, such considerations highlights the importance of Life History as a methodology that reveals many knowledge, experiences that constitute the life of those ones who do the education.